Two retroviruses packaged in one cell line can combined inhibit the replication of HIV-1 in TZM-bl cells - Liang, Zhipin (Virol Sin, 2012)
The cellular protein tetherin tethers the HIV-1 viral particles on the cellular membrane to inhibit the replication of HIV-1. However, the HIV-1 accessory protein Vpu counteracts the antiviral function of tetherin. In this study, two retroviral vector plasmids were constructed. One inhibited the vpu gene expression; the other one over-expressed the tetherin. Both retroviral vector plasmids could be packaged in the packaging cell line PT67 to obtain the corresponding retroviruses. The retroviral vector plasmids’ functions of tetherin over-expression or vpu-RNAi were detected at the cell level. Retroviral vector plasmids were transfected to PT67 cells at different ratios from 0T3V to 3T0V, and then mixed retroviruses were harvested. The antiviral functions of mixed retroviruses were detected in HIV-1 infected TZM-bl cells. The results showed that packaged mixed retroviruses could repress the replication of HIV-1 in TZM-bl cells.